Hubungan Usia, Lama Kerja dan Tingkat Pencahayaan dengan Kelelahan Mata (Astenopia) pada Penjahit di Kelurahan Kuanino Kota Kupang - Jeanet Laureandra Pabala; Anderias Umbu Roga; Agus Setyobudi (Universitas Nusa Cendana, 2021)
Theeeye fatigue experienced by tailors due to sewing is one of the jobs that requires a great deal of accuracy because the shape and size of the work object is very close and small, so the eye has to work extra to avoid mistakes. Eye fatigue that occurs in tailors can interfere with vision and increase the risk of errors or accidents while working so that it can reduce work productivity. The purpose of this study was to analyze the relationship between age, length of work and lighting levels with eye fatigue of tailors in Kuanino Village, Kupang City. The reason for choosing this location is because the location of this research is a place where there are many sewing business activities. This type of research is analytic quantitative research with a cross sectional study design. This research was conducted from March 2020 when the initial data was collected until October 2020 when the research activities were carried out. The population in this study were all tailor workers in Kuanino Village with a total of 54 people consisting of men and women. The sample in this study used a total sampling so that all the tailors in the Kuanino area, totaling 54 people, were sampled. The results showed relationship between age (0.011), length of work (0.004) and lighting (0.004) with eye fatigue (astenopia) in tailors in Kuanino Village, Kupang City. It is hoped that the tailors will be able to pay attention and take advantage of the level of lighting and the duration or working time with the aim of resting the eyes so that they are not too focused on staring at the object and can take a short break in order to reduce complaints of eye fatigue.